2021
DOI: 10.3389/fpsyg.2021.623687
|View full text |Cite
|
Sign up to set email alerts
|

The Trickle-Down Effect of Leaders’ VWGB on Employees’ Pro-Environmental Behaviors: A Moderated Mediation Model

Abstract: Although previous research has highlighted the positive effect of leaders’ voluntary workplace green behavior (VWGB), limited research attention has been given to empirically testing how and when such behavior produces trickle-down effects. Taking a role model perspective and drawing on social identity theory, this research aims to fill this gap by proposing and testing the mechanism and boundary conditions of the influencing processes whereby leaders’ VWGB can trickle down to employees’ pro-environmental beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
1
5
0
2
Order By: Relevance
“…Thus, H1 which hypothesized that environmental leadership is positively related to green organizational identity was supported (β = 0.29, t = 2.47; p < 0.001). This finding is consistent with previous studies that such contextual factors as green-oriented leadership and leaders' behaviors can be beneficial to the development of flowers' identity (Wu et al, 1292). This implies that when employees perceive that their supervisors are enacting environmental leadership approach, they are likely to strengthen their green identity with their organizations.…”
Section: Hypotheses Testsupporting
confidence: 91%
“…Thus, H1 which hypothesized that environmental leadership is positively related to green organizational identity was supported (β = 0.29, t = 2.47; p < 0.001). This finding is consistent with previous studies that such contextual factors as green-oriented leadership and leaders' behaviors can be beneficial to the development of flowers' identity (Wu et al, 1292). This implies that when employees perceive that their supervisors are enacting environmental leadership approach, they are likely to strengthen their green identity with their organizations.…”
Section: Hypotheses Testsupporting
confidence: 91%
“…That is, we find that groups and colleagues, independent of managers, provide more opportunities for employees to follow their leaders’ environmental servant characteristics and their own identification with green issues to behave more environmentally. Thus, we contribute to the knowledge that environmentally-specific servant leadership may differ in employees’ perceptions of their organization and coworkers’ green-related characteristics ( Dumont et al, 2017 ; Wu et al, 2021 ). In this way, we address scholars’ call to explore the boundary condition of organizational and coworkers’ attitudes, norms and actions as they affect employees ( Tariq et al, 2016 ).…”
Section: Discussionmentioning
confidence: 96%
“…Specifically, a research stream suggests that since leaders and managers provide employees with direct supervision and guidance during their working hours (Vecchio and Boatwright, 2002;Ogunfowora et al, 2021), from the perspective of the leadership approach, employees' environmentally oriented behaviors in the workplace are significantly influenced by their direct leaders. Accumulated evidence has consistently shown that leadership styles such as displaying and stressing environmental issues can encourage followers to generate environmental behaviors (Robertson and Barling, 2013;Cai et al, 2020;Wu et al, 2021). Notably, environmentally-specific servant leadership has recently attracted scholars' attention in the service industry (Afsar et al, 2018;Tuan, 2019;Aboramadan et al, 2021) by indicating the specific characteristics of leaders who serve the community in an environmental manner.…”
Section: Introductionmentioning
confidence: 99%
“…Addressing this research gap, the aim of this study is to examine how leaders’ psychological need satisfaction trickles down to the psychological need satisfaction of their employees. Trickling down’ refers to interaction patterns or perceptions that cascade to different levels in the organization ( Ambrose et al, 2013 ; Jeuken, 2016 ; Jiang and Lin, 2021 ; Wu et al, 2021 ; Zhong et al, 2021 ). Indeed, psychological need satisfaction might be an important element in determining how leaders act and subsequently on how employees come to evaluate and react to leaders ( Decuypere and Schaufeli, 2020 , 2021 ).…”
Section: Introductionmentioning
confidence: 99%